Pengaruh Accrual Earnings Management dan Real Earnings Management terhadap Kinerja Perusahaan dengan Struktur Kepemilikan sebagai Variabel Pemoderasi - Muhammad Syafiqurrahman; Dian Antony (Jurnal Akuntansi dan Bisnis, 2013)
This research aims to examine the effect of accrual earnings management and real earnings management on firm performance and examine the influence of of ownership structure in moderating the relationship between accrual earnings management and real earnings management to corporate performance. Companies that do accrual or real earnings management is expected to report good performance. Accrual earnings management is measured using discretionary accruals, and real earnings management is calculated by summing the standardized variables of abnormal CFO, abnormal production cost, and abnormal discretionary expense, as well as ownership structure in this research can be divided into concentrated ownership structure and ownership structure spread. The sample in this study were non-financial public company listed on the Stock Exchange and obtained a sample of 118 firms with observations for 4-year period (2004-2007). This study obtained evidence that accrual earnings management does not affect the performance of the company, while real earnings management affects firm performance. Ownership structure does not affect the relationship between accrual earnings management with the company's performance, but the ownership structure weaken the relationship between real earnings management to corporate performance.